Profitability and Company Value with Good Corporate Governance as a Moderating Variable - Yusran Bachtiar; Ananda Putri (Economos : Jurnal Ekonomi dan Bisnis, 2025)
This study aims to examine the effect of profitability, proxied by Return on Assets (ROA) and Return on Equity (ROE), on firm value, proxied by Tobin's Q, with Good Corporate Governance (GCG) as a moderating variable represented by the proportion of independent commissioners. The research is quantitative, using a sample of 18 companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) from 2022 to 2024, selected through purposive sampling. Data analysis used panel data regression with the Fixed Effect Model (FEM) and Moderated Regression Analysis (MRA). The results show that ROA has a negative and significant effect on firm value, while ROE has a positive and significant effect. GCG does not moderate the relationship between ROA and firm value but significantly moderates the relationship between ROE and firm value. These findings indicate that the effectiveness of GCG, particularly the proportion of independent commissioners, has not been optimal in strengthening the relationship between profitability and firm value as a whole .